Chooser Option Pricing based on Black-Scholes Model and Monte-Carlo Simulations - Ren, Shaoyi; Zhang, Xinyi (BCP Business & Management, 2022)
Since February 2022, the intensification of the Ukrainian conflict has triggered significant impacts on financial market. Huge changes in supply and demand have led to a spike in stock volatility, which resulted in the growth in risk aversion among investors. The gold is regarded as a safe haven asset and has hedge function in the stock markets. In this study, a Monte-Carlo pricing simulation based on Black-Scholes model for chooser option was investigated using the underlying asset of gold. The gold price and volatility index were sourced from Yahoo Finance website and the Chicago Board Options Exchange (CBOE). According to the analysis, the present value of the average return for one-month chooser option is simulated as $58.91, using the initial gold price of $1965.10 and the strike price of $1977.3. The present value of the average return for one-month chooser option is significantly higher than traditional call or put options. According to the sensitivity analysis, the return of chooser option under the pricing model adopted is not sensitive to the changes in volatility and time, which indicates that this pricing model is able to resist to risks and play a better role in a high-volatility market. These results shed light on the optimization of investment portfolio under complex situations. The utilization of a new pricing method paved a path for the research of exotic options and the state-of-art applications of them in the financial innovation procedures.